SOCIOLINGUISTIC STUDY NARRATIVE STRUCTURE AND LANGUAGE FUNCTION IN CATCH ME IF YOU CAN - Muhammad Rahman Darmawan; Muhammad Rafi Ikhsandi; Yanti Rosalinah (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Language plays a central role in shaping and legitimizing professional identity across various social interactional contexts. This study aims to examine how the character Frank Abagnale Jr. constructs and sustains multiple professional identities through language use in the film Catch Me If You Can (2002). The analysis focuses on patterns of linguistic variation that emerge when the main character impersonates a pilot, a doctor, and a lawyer, with particular attention to register management, speech style adaptation, and language functions within institutional settings. This research adopts a descriptive qualitative approach by analyzing selected dialogues transcribed from key scenes in the film. The analysis involves identifying lexical choices, levels of formality, interactional patterns, and communicative purposes that reflect the professional demands of each assumed role. The findings indicate that language use aligned with professional norms and expectations through the deployment of technical terminology, formal registers, and authoritative speech styles plays a crucial role in shaping perceptions of competence and gaining social recognition. These findings underscore that language functions as a primary performative resource in the construction of professional identity, in which membership and legitimacy within professional communities are interactionally achieved rather than solely determined by formal qualifications. ABSTRAK Bahasa memiliki peran sentral dalam membentuk serta melegitimasi identitas profesional dalam berbagai situasi interaksi sosial. Penelitian ini bertujuan untuk mengkaji bagaimana tokoh Frank Abagnale Jr. membangun dan mempertahankan beragam identitas profesional melalui penggunaan bahasa dalam film Catch Me If You Can (2002). Kajian difokuskan pada praktik variasi bahasa yang muncul ketika tokoh utama menyamar sebagai pilot, dokter, dan pengacara, dengan menyoroti pengelolaan register, penyesuaian gaya tutur, serta fungsi bahasa dalam konteks institusional. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan menganalisis dialog-dialog terpilih yang ditranskripsikan dari adegan penting dalam film. Analisis dilakukan melalui identifikasi pilihan leksikal, tingkat formalitas, pola interaksi, dan tujuan komunikatif yang mencerminkan tuntutan profesional masing-masing peran. Hasil penelitian menunjukkan bahwa penggunaan bahasa yang selaras dengan norma dan ekspektasi profesi tertentu melalui pemanfaatan istilah teknis, register formal, dan gaya tutur berotoritas berperan penting dalam membangun persepsi kompetensi dan memperoleh pengakuan sosial. Temuan ini menegaskan bahwa bahasa berfungsi sebagai perangkat performatif utama dalam konstruksi identitas profesional, di mana keanggotaan dan legitimasi dalam komunitas profesional dibentuk secara interaksional, bukan semata-mata ditentukan oleh kualifikasi formal.